The great leprechaun chase eaudiobook - Dean, James (Pete the Cat., 2020)
New York Times #1 Bestseller! New York Times bestselling author James Dean takes us on a St. Patrick's Day adventure with Pete the Cat as Pete discovers how lucky he actually is! It's St. Patrick's Day, and it's also the grand opening of Pete the Cat's leprechaun catching business. Pete gears up to trap a leprechaun for his friends! But catching a leprechaun is never easy—especially if it's Clover, who's full of tricks. Will luck be on Pete's side? Or will Pete learn luck is actually something earned?